2017
DOI: 10.3390/jcm6120113
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Similarities and Differences in the Relationship between Beta Cell Mass and Diabetes

Abstract: Recent evidence has revealed that a change of functional beta cell mass is an essential factor of the pathophysiology of type 2 diabetes (T2DM). Since beta cell dysfunction is not only present in T2DM but also progressively worsens with disease duration, to preserve or recover functional beta cell mass is important in both prevention of the development of T2DM and therapeutic strategies for T2DM. Furthermore, ethnic difference in functional beta cell mass may also need to be taken into account. Recent evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 44 publications
(54 reference statements)
1
35
0
Order By: Relevance
“…Although impaired β‐cell function and insulin resistance are both common features of T2D, there appear to be differences across ethnicities in its pathophysiology 6 . The Western T2D population is characterized by rising BMI, 5‐8 increasing insulin resistance and compensatory but ineffective hyperinsulinaemia. In the Japanese population, T2D is characterized by a prominent defect in insulin secretion, and a relatively mild increase in insulin resistance 9 .…”
Section: Demographics and Clinical Characteristics Of Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although impaired β‐cell function and insulin resistance are both common features of T2D, there appear to be differences across ethnicities in its pathophysiology 6 . The Western T2D population is characterized by rising BMI, 5‐8 increasing insulin resistance and compensatory but ineffective hyperinsulinaemia. In the Japanese population, T2D is characterized by a prominent defect in insulin secretion, and a relatively mild increase in insulin resistance 9 .…”
Section: Demographics and Clinical Characteristics Of Type 2 Diabetesmentioning
confidence: 99%
“…As β‐cell function declines, deterioration in glucose homeostasis progresses from the initial loss of postprandial plasma glucose control to elevation of fasting plasma glucose (FPG) 11 . Growing evidence suggests that individuals of East Asian descent, including people from Japan, have less β‐cell functional capacity compared with white people 6,9,12,13 . Therefore, treatment strategies that preserve β cells early in the course of diabetes are particularly critical for the Japanese population 9 .…”
Section: Demographics and Clinical Characteristics Of Type 2 Diabetesmentioning
confidence: 99%
“…4 While the dual issues of reduced insulin sensitivity and declining beta-cell function are known factors in T2D pathophysiology, the relative contributions of these factors appear to differ between ethnic groups. [5][6][7][8] In the Japanese population, T2D is characterized by a prominent decline in beta-cell function and insulin secretion, and a relatively small reduction in insulin sensitivity. 5 The importance of controlling postprandial hyperglycaemia in Japanese people has been well recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Aradillas-García et al found, however, that during childhood and adolescence, insulin concentrations and HOMA-IR exhibited a gradual increase with age [86]. This discrepancy in results may be due to multiple factors, including ethnicity [87] [88] [89] and confounding factors associated with aging such as obesity, decreased physical activity, medications and co-morbidities. World Journal of Cardiovascular Diseases…”
Section: Fernström Et Al Found An Inverse Association Between Homairmentioning
confidence: 99%